Cover: Journal of Basic Microbiology. 9/2016. (6th September 2016) - Unknown
Abstract : Enzyme‐substrate complex formation activated by metal ions. Pyranose ring opened by the formation of hydrogen bond (white dotted lines) between imidazole group of His‐101 and the hydroxyl group of C5, while rest of the active site and metal binding sites' residues maintain the structural orientation of the intermediate formed in the active site of the enzyme with substrate which is assisted by metal binding sites (Predicted by PatchDock, v.beta 1.3; created by UCSF Chimera, v.1.10.2). (Figure: Bilqees Fatima, Institute of Industrial Biotechnology (IIB), GC University, Lahore, Pakistan)